2018
DOI: 10.1108/jpbm-07-2016-1265
|View full text |Cite
|
Sign up to set email alerts
|

In for a penny, in for a pound? Exploring mutual endorsement effects between celebrity CEOs and corporate brands

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 153 publications
1
25
0
Order By: Relevance
“…Before being extending to other categories, the self-marketing concept was originally adopted when dealing with celebrities (e.g. Lim and Lim 2016;Moulard et al 2015;Rein et al 2007;Kowalczyk and Pounders 2016), politicians, business managers (Schawbel 2009;Shepherd 2005;Scheidt et al 2018) and also non-profit organizations' leaders (Nolan 2015).…”
Section: Building Personal Brand In the Social Media Contextmentioning
confidence: 99%
“…Before being extending to other categories, the self-marketing concept was originally adopted when dealing with celebrities (e.g. Lim and Lim 2016;Moulard et al 2015;Rein et al 2007;Kowalczyk and Pounders 2016), politicians, business managers (Schawbel 2009;Shepherd 2005;Scheidt et al 2018) and also non-profit organizations' leaders (Nolan 2015).…”
Section: Building Personal Brand In the Social Media Contextmentioning
confidence: 99%
“…Now consumers and companies do not see only products and services as brands, but many other entities are also approached as branded entities. Humans in the form of celebrities (Kowalczyk and Pounders, 2016), politicians (Guzmán et al, 2015;Bigi et al, 2016), artists (Kucharska and Mikołajczak, 2018), managers (Bendisch et al, 2013) and celebrity CEOs (Scheidt et al, 2018), athletes (Carlson and Donavan, 2013), bloggers (Delisle and Parmentier, 2016) or as simple individuals (Guzmán et al, 2015) see themselves and are seen by others as brands in their own right. Countries, regions and cities are also seen as brands (Rojas-Méndez, 2013) and they are very complex in their makeup and approach.…”
Section: Other Things Have Changedmentioning
confidence: 99%
“…In this sense, our findings highlight how internal endorsement refers to the corporate brand more than the product or the brand (compared to celebrity endorsement), and thus, has the capacity to influence the corporate brand perception. Although recent research (Scheidt et al , 2018) showed that famous CEOs impact the corporate brand image, our research enriches knowledge about the influence of unfamiliar CEOs and employees. In this sense, the exploratory and inclusive perspective (famous CEO, unfamiliar CEO and employees) adopted in this research allows us to suggest that internal endorsement has the ability to speak for the company and nourish the corporate brand image.…”
Section: Discussionmentioning
confidence: 74%